CONCORDANCES ÉTYMOLOGIQUES ET LEXICO-SÉMANTIQUES ENTRE LE FRANÇAIS RÉGIONAL ET LE ROUMAIN - Adrian CHIRCU (Studia Universitatis Babeş-Bolyai. Philologia, 2020)
Etymological and Lexical-Semantic Concordances Between Regional French and Romanian language. In our study, we propose to discuss about some lexical-semantic concordances between regional French and Romanian language, that can be explained through the heritage of Latin lexis. Having the purpose of building an objective analysis, we referred to a wide French regionalism dictionary and we selected a number of terms, whose significations were subsequently related to some meanings of homologous words in Romanian language. Furthermore, we kept permanently the reference to their Latin etymons and to their signification. We considered as well some aspects of word formation in Latin and the later development that took place. Pursuant to the lexical unities’ comparison, we discovered that there is certainly a conservationism of regional French and of Romanian towards Latin, from both semantic and structural perspectives.